Expectant management for abdominal pregnancy - Koji Yasumoto; Yukiyasu Sato; Yusuke Ueda; Takuma Ito; Hiromi Kawaguchi; Masataka Nakajima; Akira Muneshige (Wolters Kluwer Medknow Publications, 2017)
This is the first English language report describing the expectant management for abdominal pregnancy. The patient was a 31-year-old multiparous woman who was transferred to our hospital on suspicion of ectopic pregnancy. Her serum human chorionic gonadotropin was positive, and a poorly-vascularized mass measuring about 4 cm was visualized in the Douglas pouch by transvaginal ultrasonography, as well as by pelvic magnetic resonance imaging. Because the bilateral adnexa were apparently intact, she was diagnosed with abdominal pregnancy, and expectant management was commenced. Unexpectedly, the mass remained in situ for nearly 3 years after her serum human chorionic gonadotropin tested negative. Laparoscopic removal of the mass was finally required because of persistent defecation pain. This case illustrates that some abdominal pregnancies can be managed expectantly, as is the case with tubal pregnancies. During the expectant management, however, it should be considered that the abdominal pregnancy mass may persist for a longer period and cause moderate symptoms necessitating surgical removal.